1985
DOI: 10.1159/000124057
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Growth Hormone Release by Vasoactive Intestinal Peptide and Peptide PHI in Rat Anterior Pituitary Reaggregates

Abstract: In superfused rat anterior pituitary cell reaggregates, cultured for 5 days in serum-free defined medium, vasoactive intestinal peptide (VIP) concentration-dependently stimulated prolactin (Prl) release but had only a marginal effect on growth hormone (GH) release. When reaggregates were cultured in the presence of 80 nM dexamethasone (Dex) VIP strongly stimulated GH release from a concentration as low as 0.1 nM VIP did not stimulate LH release. Peptide PHI also stimulated GH release but thyrotropin-releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

1986
1986
1998
1998

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The results were in agreement with previous reports on in vitro studies on rats [13]. PHI is reported, however, to induce GH release from aggregated rat pituitary cells in culture only after treatment with dexamethasone [12].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results were in agreement with previous reports on in vitro studies on rats [13]. PHI is reported, however, to induce GH release from aggregated rat pituitary cells in culture only after treatment with dexamethasone [12].…”
Section: Discussionsupporting
confidence: 93%
“…As regards the higher potency in GHRH-stimulated bovine GH release than that obtained with VIP, the present study coincided with reports of previous studies on superfused rat pituitary reaggregated cells [12], and on perifused bovine anterior pituitary tissues [15]. It has been reported that the GH releasing effects of GHRH were maintained longer than that of VIP, suggesting that the somatotrophs might be stimulated to release GH for hours by a short period of GHRH action [15].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…commun. ], have been shown to antagonize each other in cultured pituitary reaggregates [8]. Treatment with DA agonists reduced or suppressed the paradoxical G il response to TRH in constitutionally tall adolescents [12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to GHRH and SRIH. other peptidergic mechanisms are also involved in the regulation ofGH: for example, vasoactive intestinal peptide and peptide histidine isoleucine [10] stimulate GH release from cultured rat anterior pituitary cells. Insulin-like GH, GH itself and SRIH reduce the secretory activity of human somatotrophs in vitro [II] and in vivo [12], These effects are either direct ef fects upon the pituitary cells or mediated by inhibitory or stimu latory activity upon suprapituitary GHRH and SRIH release.…”
mentioning
confidence: 99%